Genome-wide copy number variant screening of Saudi schizophrenia patients reveals larger deletions in cases versus controls - Abumadini, Mahdi S.; Al Ghamdi, Kholoud S.; Alqahtani, Abdullah H.; Almedallah, Dana K.; Callans, Lauren; Jarad, Jumanah A.; Cyrus, Cyril; Koeleman, Bobby P. C.; Keating, Brendan J.; Pankratz, Nathan; Al-Ali, Amein K. (Frontiers in Molecular Neuroscience, 2023)
Genome-wide association studies have discovered common polymorphisms in regions associated with schizophrenia. No genome-wide analyses have been performed in Saudi schizophrenia subjects. Genome-wide genotyping data from 136 Saudi schizophrenia cases and 97 Saudi controls in addition to 4,625 American were examined for copy number variants (CNVs). A hidden Markov model approach was used to call CNVs. CNVs in schizophrenia cases were twice as large on average than CNVs in controls (p = 0.04). The analyses focused on extremely large >250 kilobases CNVs or homozygous deletions of any size. One extremely large deletion was noted in a single case (16.5 megabases on chromosome 10). Two cases had an 814 kb duplication of chromosome 7 spanning a cluster of genes, including circadian-related loci, and two other cases had 277 kb deletions of chromosome 9 encompassing an olfactory receptors gene family. CNVs were also seen in loci previously associated with schizophrenia, namely a 16p11 proximal duplication and two 22q11.2 deletions. Runs of homozygosity (ROHs) were analyzed across the genome to investigate correlation with schizophrenia risk. While rates and sizes of these ROHs were similar in cases and controls, we identified ten regions where multiple cases had ROHs and controls did not.